The Prevalence and Antibiotic Resistance of Methicillin-Resistant Staphylococcus aureus (MRSA) in Milk and Dairy Products in Balikesir, Turkey - EKTIK, NISANUR; GÖKMEN, MUKADDERAT; ÇIBIK, RECEP (Journal of the Hellenic Veterinary Medical Society, 2018)
Methicillin-Resistant Staphylococcus aureus is an important pathogen that causes severe infections in humans and animals. The aim of this study was to determine the prevalence and the antimicrobial profile of methicillin-resistant S. aureus (MRSA) in cow bulk tank milk and dairy products in the region of Balikesir in Turkey. Of 175 milk and dairy products’ samples, 26 were found to be positive for coagulase-positive staphylococci and 3 (2 samples from cow bulk tank milk and 1 sample from tulum cheese) were MRSA phenotypically being resistant against both oxacillin and cefoxitin. Among these, 17 were confirmed as S. aureus by the detection of nuc gene and one as MRSA carrying the mecA gene. All MRSA isolates were found to be also resistant against ampicillin, penicillin and sulfamethoxazole-trimethoprim. Consequently, even though the prevalence of MRSA in cow bulk tank milk and dairy productswas relatively low (1.70%), it may pose serious risks in terms of food safety and public health. In order to prevent the prevalence of MRSA in dairy products, hygienic measures, especially in terms of personal hygiene and disinfection of equipment in all stages of dairy production, should be taken, and HACCP and GMP regulations should be implemented.